Experiences of newly qualified professional nurses in a public hospital in the Gauteng Province - Ngwenya, Nelisiwe (My University, 2021)
Background: The first-year experiences of newly qualified professional nurses are regarded as the most important in their careers. Literature clearly indicates that newly qualified professional nurses both have a stressful experience and feel unprepared for their roles within the healthcare system. These experiences lead to a high number of newly qualified professional nurses leaving the nursing profession. Purpose/Aim: The purpose of this study was to explore and describe the experiences of newly qualified professional nurses in a regional hospital in the Gauteng Province. Methodology: A qualitative research approach and descriptive research design were used to gain insight into the first-year experiences of professional nurses at a public hospital in Gauteng Province. The population included all professional nurses employed at the institution during 2016/2017 who worked at the selected research site. Participants were sampled through purposive sampling and data collected using unstructured interviews to collect information. Setting: Data was collected in a regional public hospital in the Gauteng Province. Data Analysis: Data analysis was conducted using qualitative content analysis. Data was organised, a general sense was developed, data was coded by identifying common words and phrases from the information collected. Four themes and four sub-themes emerged from the data and were linked to the research questions and objectives. Results: The results of this study revealed that professional nurses experienced both positive and negative experiences during their first year of employment. Newly qualified professional nurses were excited with their new role. They felt ready and prepared to take up responsibility in their new environment. The planned orientation programme introduced the new professional nurses to the new environment. The orientation period was followed by a reality check in the individual units where professional nurses were placed. The rotation system exposed newly qualified professional nurses to different units. The rotation system assisted the newly qualified professional nurses to gain experience and increased their skills. They experienced the work environment as being totally different from the environment they trained in. They were exposed to the realities of overseeing units and the challenges that come with the new responsibilities. This resulted to newly qualified professional nurses questioning their decision to choose nursing as the preferred profession
A research report submitted in fulfilment of the requirements for the degree Master of Science in Nursing to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2021